Juridical Review of the Implementation of Foreign Arbitration Awards in Indonesia in the Perspective of Constitutional Court Ruling Number 4/PUU-XXII/2024 - Adhitya Anugrah Nasution; Faisal Santiago (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The implementation of foreign arbitration awards in Indonesia from the perspective of Constitutional Court Decision Number 4/PUU-XXII/2024 is crucial in both international and domestic legal contexts. This article provides a strong legal basis for arbitration usage in resolving cross-border business disputes in Indonesia, both domestically and internationally. The research contributes to the legal field by offering an in-depth normative juridical analysis of how unfamiliar discretion grants are executed in Indonesia. Data analysis was carried out descriptively and qualitatively. The research topic, namely, the Juridical Review of the Implementation of Foreign Arbitration Decisions in Indonesia in the Perspective of Sacred Court Choice Number 4 is analyzed using deductive methods, which entail deriving conclusions from general to specific, particularly regarding the research topic. In this specific situation, a juridical survey of the execution of unfamiliar mediation grants in Indonesia becomes vital to comprehend the effect of established Court Choice number 4 on international arbitration practices, legal certainty, and the investment environment in Indonesia.